Modelling and uncertainty analysis of Seebeck coefficient measurements by using the finite element method. (2021) - Huang, K.; Edler, F.; Haupt, S.; Ziolkowski, P.; Stiewe, C.; Müller, E.
Abstract: The present work is focused on the determination of single uncertainty contributions of Seebeck coefficient measurements of semiconducting bulk materials. Different simulations are performed to quantitatively explore effects and their influence on the measurement uncertainty. The following effects are studied by the finite element method (FEM): the choice of data sets from transient thermoelectric signals, the influence of asynchronous voltage and temperature measurements, and the so called "finger" effect, which represents the falsification of a measurement caused by the contact resistance between a sensor and a sample. The FEM allows the exploration of the data space under ideal conditions, which are hardly obtainable in real experiments. The results of the simulations are used to quantify the corresponding uncertainty contributions.